Correlation of lateral ventricular size and deep gray matter volume in MRI at term equivalent age with neurodevelopmental outcome at a corrected age of 24 months and with handedness in preterm infants - Storbeck, Tobias; Bruns, Nora; Weiss, Christel; Felderhoff-Mueser, Ursula; Mueller, Hanna (European Journal of Pediatrics, 2020)
The aim of this study was to correlate ventricular size and volumes of deep gray matter (DGM) in MRI at term equivalent age (TEA) with outcome at a corrected age of 24 months in preterm infants and with handedness. Seventy-three infants born before 32 weeks of gestation or with birth weight < 1500 g were included in this retrospective analysis and measurement of lateral ventricles, and DGM was performed on MRI scans. The left lateral ventricle was significantly larger than the right lateral ventricle (p = 0.001). There was no correlation between volumes of the right and left ventricles and the DGM volume (p = 0.207 and p = 0.597, respectively), nor with the head circumference at TEA (p = 0.177 and p = 0.976, respectively). The total volume of both lateral ventricles did not correlate with Mental Develomental Index (MDI, p = 0.336) or Psychomotor Developmental Index (PDI, p = 0.650) score (Bayley Scales of Infant Development, BSID II). However, a correlation of total DGM volume with birth weight (p = 0.0001; r = 0.437), head circumference at TEA (p < 0.0001; r = 0.640), MDI (p = 0.029; r = 0.310), and PDI (p = 0.002; r = 0.456) was observed. No significant difference between right- and left-handed infants was seen in relation to volumes of both lateral ventricles and of DGM.Conclusion: DGM volume at TEA was significantly associated with the outcome at a corrected age of 24 months. Handedness did not correlate with DGM or lateral ventricle size.What is Known:• White matter injury as well as altered development of deep gray matter is associated with neurodevelopmental disability in preterm infants.• No study analyzed the association between deep gray matter volume or volumes of lateral ventricle and handedness in former preterm infants so far.What is New:• Volume of deep gray matter, but not lateral ventricular size was significantly associated with outcome at a corrected age of 24 months in preterm infants.• There was no correlation of handedness with volumes of lateral ventricular size or with deep gray matter volumes.
EVALuna2:210492